1997
DOI: 10.1074/jbc.272.20.13013
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of the Small Subunit of Human DNA Polymerase δ

Abstract: DNA polymerase ␦ is a heterodimer consisting of a catalytic subunit of 125 kDa and a small subunit of 50 kDa (p50). We have overexpressed p50 in Escherichia coli and have characterized the recombinant protein. p50 was readily overexpressed using the pET vector as an insoluble protein. A procedure was developed for its purification and renaturation. Examination of the physicochemical properties of renatured p50 showed that it is a monomeric protein with an apparent molecular weight of 60,000, a Stokes radius of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…The pol ␦ core purified from calf thymus consists of two subunits: p125 and p50 (3). However, we have found that recombinant p125 catalytic subunit alone can only be stimulated by PCNA by 2-fold at most, while the overexpressed p125/p50 heterodimer is stimulated much less than pol ␦ purified by immunoaffinity chromatography (15,16). These findings suggest that additional factor(s) which may be removed during protein purification are required for a full PCNA response in our assay.…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…The pol ␦ core purified from calf thymus consists of two subunits: p125 and p50 (3). However, we have found that recombinant p125 catalytic subunit alone can only be stimulated by PCNA by 2-fold at most, while the overexpressed p125/p50 heterodimer is stimulated much less than pol ␦ purified by immunoaffinity chromatography (15,16). These findings suggest that additional factor(s) which may be removed during protein purification are required for a full PCNA response in our assay.…”
mentioning
confidence: 45%
“…prokaryotic or lower eukaryotes such as yeast. Recently, expression systems for the p125 (15,24,25), the p50 subunit (16), and the recombinant heterodimer have been developed (26). The p50 subunit has no known enzymatic functions, but has been shown to be required for the response of the p125 subunit to PCNA (16,26).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme we used in this study was purified by the immunoaffinity chromatography and gel filtration, and may contain other components besides the two subunit form that is isolated after stringent conventional chromatography (19). 4 In our hands, the pol ␦ p125 subunit overexpressed in Sf9 cells could be stimulated only 5-fold with PCNA in the presence of recombinant p50 expressed in E. coli (40). Polymerase ␦ obtained by co-expression of the p125 and p50 subunits (pol ␦ core) in the baculovirus system could be stimulated by PCNA at most 8-fold, far less than the stimulation obtained by the holoenzyme prepared from the immunoaffinity column.…”
Section: Table I Summary Of Mutations In the Interdomain Connector Lomentioning
confidence: 92%
“…Functional studies with recombinant p125 from human (28,39,40), mouse (41), and S. pombe (42) sources have shown that DNA synthesis catalyzed by p125 alone is not significantly stimulated by PCNA. On the other hand, PCNA was shown to stimulate the activity and processivity of the recombinant human heterodimer to the same extent as the native two-subunit enzyme isolated from calf thymus (28), suggesting the possibility that the interaction of PCNA with pol ␦ is mediated through the small subunit.…”
mentioning
confidence: 99%